Current Researches, Rationale, Plausibility, and Evidence Gaps on Metformin for the Management of Hypertensive Disorders of Pregnancy - Zhang, Yang; Liu, Xiaoxia; Yang, Liu; Zou, Li (Frontiers in Pharmacology, 2020)
Hypertensive disorders of pregnancy (HDP) are a group of morbid pregnancy complications and preeclampsia (PE) is the most common subclassification among them. PE affects 2–8% of pregnancies globally and threatens maternal and fetal health seriously. However, the only effectual treatment of PE, as yet, is the timely termination of pregnancy, though along with raised perinatal risks. Hence, more emerging therapies for PE management are in urgent need. Originally introduced as the first-line therapy for type 2 diabetes mellitus, metformin (MET) has now been found in clinical trials to significantly reduce the incidences of gestational hypertension and PE in pregnant women with PE-related risks, including but not limited to pregestational diabetes mellitus, gestational diabetes mellitus, polycystic ovary syndrome, or obesity. Additionally, existing clinical data has preliminarily ensured the safety of taking MET during human pregnancies. Relevant lab studies have indicated that the underlying mechanism includes the angiogenesis promotion, endothelial protection, anti-inflammatory effects, and particularly the protective effects on trophoblast cells against the risk factors, which are beneficial to placental development. Together with the global availability, easy administration, and low cost, MET is expected to be a promising option for the prevention and treatment of PE. Nevertheless, there are still some limitations in current studies, and the design of the relevant research scheme is supposed to be further improved in the future. Herein, we summarize the relevant clinical and experimental researches to discuss the rationale, safety and feasibility of MET for the management of HDP. At the end of the article, gaps in the current researches are proposed. Concretely, experimental MET concentration and PE models should be chosen cautiously. Besides, the clinical trial protocol should be further optimized to evaluate the reduction in the prevalence of PE as a primary endpoint. All of those evidence gaps may be of guiding significance to improve the design of the relevant experiments and clinical trials in the future.